A rare missense p.C125Y mutation in the TNFRSF1A gene identified in a Chinese family with tumor necrosis factor receptor-associated periodic fever syndrome - Qian, Mengqing; Zhou, Jingyu; Wu, Jing; Zhang, Haocheng; Yu, Shenglei; Xu, Haoxin; Yang, Yixuan; Zhou, Feiran; Yang, Qingluan; Shao, Lingyun; Zhang, Wenhong; Jiang, Ning; et al. (Frontiers in Genetics, 2024)
Background Tumor necrosis factor receptor-associated periodic syndrome (TRAPS) is a rare autosomal dominant disorder with a low incidence in Asia. The most frequent clinical manifestations include fever, rash, myalgia, joint pain and abdominal pain. Misdiagnosis rates are high because of the clinical and genetic variability of the disease. The pathogenesis of TRAPS is complex and yet to be fully defined. Early genetic diagnosis is the key to precise treatment. Methods In this study, a Chinese family with suspected TRAPS were analyzed by genome-wide SNP genotyping, linkage analysis and targeted sequencing for identification of mutations in causative genes. To study the pathogenicity of the identified gene mutation, we performed a conservation analysis of the mutation site and protein structure analysis. Flow cytometry was used to detect TNFRSF1A shedding and quantitative real-time PCR were used to assess the activation of unfolded protein response (UPR) in the mutation carriers and healthy individuals. Results A typical TRAPS family history, with a pattern of autosomal dominant inheritance, led to the identification of a rare mutation in the TNFRSF1A gene (c.G374A [p.Cys125Tyr]) with unknown significance. The patient responded well to corticosteroids, and long-term therapy with colchicine effectively reduced the inflammatory attacks. No amyloid complications occurred during the 6-year follow-up. In silico protein analysis showed that the mutation site is highly conversed and the mutation prevents the formation of intrachain disulfide bonds in the protein. Despite a normal shedding of the TNFRSF1A protein from stimulated monocytes in the TRAPS patients with p.C125Y mutation, the expression of CHOP and the splicing of XBP1 was significantly higher than healthy controls, suggesting the presence of an activation UPR. Conclusion This is the first report of a Chinese family with the rare p.C125Y mutation in TNFRSF1A. The p.C125Y mutation does not result in aberrant receptor shedding, but instead is associated with an activated UPR in these TRAPS patients, which may provide new insights into the pathogenesis of this rare mutation in TRAPS.